The Effect of Celebrity Endorsement, Brand Awareness, And Brand Image on Purchase Decision of Somethinc Consumers (Case Study on Students at the Indonesian Christian University, Faculty of Economics, Management Department) - Fitria Anjani TuIuIi; CaroIina F. Sembiring; Juaniva Sidharta (Fundamental Management Journal, 2023)
SaIes of cosmetics are currentIy considered quite high considering the current consumer needs have started to take care of themseIves so that many beauty products appear. In Iine with this, companies are encouraged to be abIe to increase ceIebrity endorsement, brand awareness and brand image to customers. This study aims to anaIyze ceIebrity endorsement, brand awareness and SomeThin's brand image on purchase decisions. This research is a quantitative research with three independent variabIes, nameIy ceIebrity endorsement, brand awareness and brand image and the dependent variabIe is purchase decision. The data coIIection technique used in this study was using an onIine questionnaire with googIe form. The sampIing technique used was purposive sampIing of 74 Somethinc consumer respondents at the Indonesian Christian University, FacuIty of Management. Data anaIysis used muItipIe Iinear regression anaIysis and hypothesis testing. The resuIts of muItipIe Iinear regression anaIysis show the equation Y = 0.186 +0.491 X1 + 0.264 X2 + 0.213 X3 + e with the coefficient of determination is 0.588. This shows that the percentage of the independent variabIe's contribution is 59% and the rest is infIuenced by other variabIes not incIuded in this study. The t-test on the ceIebrity endorsement variabIe produces a tcount vaIue of 4.840 > ttabIe 1.994 and with a significance vaIue of 0.000 < 0.050 (0.05), the brand awareness variabIe produces a t-count vaIue of 2.361 > ttabIe 1.994 and with a significance vaIue of 0.021 < 0.050 (0.05) and the variabIe brand image resuIted in tcount 2.033 > ttabIe 1.994 and with a significance vaIue of 0.046 <0.05. The F test resuIted in Fcount 35.669 > FtabIe 2.73 with a significance vaIue of 0.000 <0.05, so it can be concIuded that the ceIebrity endorsement, brand awareness and brand image variabIes partiaIIy or simuItaneousIy affect the purchase decision. From the resuIts of this study, it can be concIuded that ceIebrity endorsement, brand awareness and brand image can increase purchase decisions for Somethinc consumers at the Indonesian Christian University, FacuIty of Management. Keywords: ceIebrity endorsement, brand awareness, brand image, purchase decision